PROMISING EARLY PLANTING AND STRESS-TOLERANT POTATO GENOTYPES FOR NORTHERN BANGLADESH - M.N. Amin (Zibeline International, 2021)
Potato is the third major food crop in the world. In Northern Bangladesh, potato production outside the regular growing season can contribute to farmers’ profit and prices can be very favorable as consumers’ demand for potatoes is greater than the decreased, off-season supply. However, potato production may be negatively affected by increased pest and disease pressure and higher soil temperature. We hypothesized that some potato varieties would have smaller tuber yield reduction when they are grown outside the normal season. The objective of this experiment was to find out promising genotypes for earlier cultivation prior to mid of November, cultivation in northern regions of Bangladesh. The trials, corresponding to very early, early, normal and late growing seasons were planted using a randomized complete block design with three replications. Germination percent, plant height, stems per hill, marketable tuber yield at 65 days, marketable tuber yield at 90 days were recorded. For yield and components of yield contributing characters Clone 13.17, BARI Alu 7(Diamant) and Arizona outperformed in all growing condition and had wider adaptability and stability of tuber yield based on Additive main effects and multiplicative interaction (AMMI).